157k views
3 votes
Which of the following is a solution to the equation 0=x^2+6x+4

User Dotdot
by
6.4k points

1 Answer

3 votes

Answer:


x=-3\pm√(5)

General Formulas and Concepts:

Pre-Alg

  • Order of Operations: BPEMDAS

Alg I

  • Standard Form: ax² + bx + c = 0
  • Quadratic Formula:
    x=(-b\pm√(b^2-4ac) )/(2a)

Explanation:

Step 1: Define

x² + 6x + 4 = 0

a = 1

b = 6

c = 4

Step 2: Find x

  1. Substitute:
    x=(-6\pm√(6^2-4(1)(4)) )/(2(1))
  2. Evaluate:
    x=(-6\pm√(36-4(1)(4)) )/(2(1))
  3. Multiply:
    x=(-6\pm√(36-16) )/(2)
  4. Subtract:
    x=(-6\pm√(20) )/(2)
  5. Simplify:
    x=(-6\pm2√(5) )/(2)
  6. Factor:
    x=(2(-3\pm√(5)) )/(2)
  7. Simplify:
    x=-3\pm√(5)
User Ivan Nesterenko
by
5.8k points